Pengaruh Job Satisfaction dan Work Environment Terhadap Perilaku Cyberloafing Pada Dinas Komunikasi, Informatika, Statistik, dan Persandian Kabupaten Mamuju - Nurhalisa; Nur Fajariani; Mu’fidatul Nurul Hajjad (Paradoks : Jurnal Ilmu Ekonomi, 2025)
This study investigates the influence of job satisfaction and work environment on cyberloafing behavior among civil servants at the Department of Communication, Informatics, Statistics, and Coding (Persandian) in Mamuju Regency. Cyberloafing, defined as the use of the internet for personal purposes during working hours, has become a pressing challenge in the digital workplace. Using a quantitative approach, data were collected through questionnaires distributed to 32 respondents, all of whom are civil servants (ASN). A total sampling method was employed, and the data were analyzed using multiple linear regression. The results revealed that job satisfaction had no significant effect on cyberloafing, with a t-value of -0.539 < 2.04522 and a significance level of 0.558 (> 0.05). Similarly, the work environment variable showed no significant effect, with a t-value of 1.270 < 2.04522 and a significance level of 0.214 (> 0.05). Simultaneously, both variables were not significant predictors of cyberloafing, as indicated by an F-value of 1.174 < 3.327 with a significance of 0.323 (> 0.05). These findings suggest that cyberloafing is influenced by other factors beyond job satisfaction and work environment. Future research should consider variables such as self-efficacy, time management, organizational culture, or technological monitoring to better explain cyberloafing in public institutions.